Immune responses to vaccine-preventable diseases among toddlers and preschool children after primary immunization and first booster in Northwestern Algiers, Algeria. Issue 6 (June 2018) - Benamrouche, Nabila; Tali Maamar, Hassiba; Chemli, Samia; Senouci, Houria; Rahal, Kheira
Abstract: Objectives: To determine immune responses to selected vaccine-preventable communicable diseases: pertussis, diphtheria and Haemophilus influenzae type b (Hib 1 ) in Algerian toddlers and preschool children after primary vaccination and first booster, recruited from three local healthcare facilities in Northwestern Algiers. Methods: The information of demographic characteristics and vaccination status were collected for each subject by questionnaire. Specific antibody levels and Hib antibody avidity were determined using commercial ELISA kits. Results: A total of eighty-one subjects aged between 19 and 55 months were studied. Almost all subjects were fully protected against diphtheria (76/81; 93.83%; 95% CI 2 : 86.35–97.33) and invasive Hib disease (29/30; 96.67%; 95% CI: 83.33–99.41), while only 20/78 (25.64%; 95% CI: 17.26–36.31) had anti-PT 3 (pertussis toxin) antibody levels above 25 IU/ml. A significant decrease of anti-PT antibody levels was observed until the age of 36 months ( p = 0.02). GMTs 4 (geometric mean titers) of anti-PT antibodies were low, but remain significantly higher in children ≤36 months of age ( p = 0.02). Both GMT and rates of ≥0.15 μg/ml, ≥1 μg/ml, and ≥5 μg/ml titers were significantly higher in Hib-vaccinated subjects ( p < 0.01). Relative Hib-avidity index (≥50%) and GMAI 5 (geometric mean avidity index) were high in both Hib-vaccinated and -unvaccinated groups. Conclusions: As shown in the present study, young children were fully protected against diphtheria and Hib, but showed low immunity to pertussis. Further sero-epidemiological studies including a large number of subjects with a wider range of age are needed to explore the immunity level in older children, adolescents and adults.